Mortality and Associated Risk Factors in Dialysis Patients with Cardiovascular Disease - Junrong Tong; Manyi Liu; Hong Li; Zhengmao Luo; Xianyang Zhong; Jun Huang; Riguang Liu; Feng He; Junzhou Fu (Karger Publishers, 2016)
Background/Aims: Although dialysis patients have a higher risk of morbidity and mortality related to cardiovascular disease (CVD) than the general population, the mortality and associated risk factors in Asian dialysis patients with CVD have not been well examined. Methods: In this prospective cohort study, mortality and risk factors were investigated in 591 dialysis patients who were recruited from two dialysis centers from May 1, 2009 to May 1, 2014. The Cox proportional hazards regression assessed adjusted differences in mortality risk. A multivariate analysis was also performed, comparing the CVD and non-CVD groups. Results: A total of 591 patients were enrolled in this study (mean age, 52.05 ± 16.46 years [SD]; 61.8% men; 20.8% with CVD), with a median follow-up of 21.9 (maximum, 72) months. The cumulative hazard of mortality was significantly higher in CVD patients (hazard ratio [HR], 1.835; 95% confidence interval [CI], 1.023-3.293; P=0.042) than in their non-CVD counterparts after adjusting for various confounders. On multivariate Cox analysis, stroke (HR, 4.574; 95% CI, 2.149-9.736; PConclusion: All-cause mortality was significantly higher in the CVD group than in the non-CVD group. Stroke is an independent risk factor for all-cause mortality in dialysis patients with CVD. These findings warrant further studies into preventive and interventional strategies.